Housing and Austerity: A Two-Way Street - Lyons, Ronan (Royal Irish Academy, 2017)
﻿Simon Wren-Lewis’s chapter in this volume outlines a general theory of austerity. Underpinning it is a desire for policymakers – as well as the social sciences – to learn from the experience of austerity over the last decade. In particular, Wren-Lewis makes the point that austerity was, at a global level, unnecessary. The asterisk to this finding relates to particular countries, where austerity at a national level was unavoidable. Ireland’s recent economic history is not only remarkable but also incredibly useful, if policymakers are to learn lessons from the experience of the last decade. The economic journey from ‘the poor man of Western Europe’ in the late 1980s, through the export-led growth of the 1990s and the credit-led growth of the early 2000s, to the sharp economic contraction in the years after 2007, contains much for other small open economic regions to learn. This is particularly true in the context of a region – Ireland – largely dependent on one city of global significance (Dublin), where that region lacks its own monetary policy and recourse to the traditional levers of trade policy to react to economic shocks. Exposed to global economic tailwinds, and later headwinds, and with an inadequate domestic policy response, two key aspects of the local economy – government spending and housing – bore much of the brunt of Ireland’s economic contraction. With Ireland once again one of Western Europe’s fastest growing economies, it is tempting for policymakers locally to assume that lessons have been learnt, or perhaps that Ireland was unlucky in its exposure to global shocks. It is the aim of this chapter to show that the poor management of two key domestically-focused sectors contributed separately and jointly to the severity of the economic correction in Ireland. In so doing, it hopes to highlight some key themes for policymakers to take away from Ireland’s experience in austerity and housing. The bulk of this chapter is organised around two key relationships. The first is the contribution that the housing sector made initially to the huge expansion in government spending and thus, by corollary, in austerity. Whereas that section focuses on the effect of housing on austerity, the next section focuses on the reverse: the impact austerity has had on the housing sector in Ireland. The penultimate section draws out the policy implications of the preceding analysis, outlining what principles should act as the foundation for housing policy into the future, after which the chapter concludes.
Debating austerity in Ireland: crisis, experience and recovery
Keywords: Austerity; Irish economy; Housing policy; Inclusive Society; International Integration; Making Ireland; Housing Markets; IRISH HOUSING SYSTEM; Urban Economics